“Where was this when I was in Physical Education?” Physical literacy enriched pedagogy in a quality physical education context - Houser, Natalie; Kriellaars, Dean (Frontiers in Sports and Active Living, 2023)
Introduction In recent years, there has been a call to restructure physical education (PE) practices and outcomes. A physical literacy enriched pedagogy approach would support this change by more intentional design of lesson planning that includes concurrent development of competence & confidence and inclusion of students of all levels of ability, leading to holistic development of the student. Despite this potential, there is little research to date that outlines PE pedagogical practices with physical literacy as a foundation. The purpose was to explore pedagogical practices and perspectives from elementary PE teachers through a physical literacy enriched pedagogy lens in a high-quality PE context. Methods One-on-one semi-structured interviews were conducted with a convenience sample of elementary PE teachers within one school division. Interviews with all participants focused on questions related to PE and physical literacy. Thematic analysis was used to analyze the data collected from the audio-recorded interviews. Results Four themes were generated based on the semi-structured interviews from six elementary PE teachers from one school division. The results identified key physical literacy enriched pedagogical practices based on four themes: supporting a holistic PE experience based upon physical literacy as an outcome; movement within and beyond PE; inclusive and individualized experiences; and physical literacy practices bringing the school community together. The findings were then connected to the physical literacy cycle and UNESCO components of quality PE. Conclusions All participants spoke to how their pedagogy focused on the holistic development and inclusion of their students based upon activation of various feedback pathways of the physical literacy cycle. The themes that emerged and subsequent insight gained from teachers went beyond existing physical literacy cycles, in particular by discussing development of students from cognitive, affective, social and creative (problem solving) perspectives, supporting an expansion to the existing physical literacy cycle as presented.